Metal and ligand effects on the stability and electronic properties of crystalline two-dimensional metal-benzenehexathiolate coordination compounds. (23rd October 2018) - Tang, Liang-Po; Tang, Li-Ming; Wang, Dan; Deng, Hui-Xiong; Chen, Ke-Qiu
Abstract: The cohesive energy, phonon spectrum and quantum molecular-dynamic simulation have been used successively to determine whether the crystalline two-dimensional (2D) metal-benzenehexathiolate (M-BHT) coordination compounds are stable or not. The electronic structures of stable M-BHTs and the corresponding inorganic semiconducting materials have been compared. From the point of view of satisfying stoichiometric ratios and saturation of chemical bonds, we designed possible planar molecular structures and demonstrated that there may be two different 2D M-BHTs, i.e. group II- and group IV- . However, the cohesive energy calculation indicates that the group IV- coordination compound cannot be obtained by thermodynamic equilibrium growth. In contrast, and from the group II- have not only thermodynamic stability, but also dynamic stability due to their phonon spectrum with no imaginary frequency. Moreover, they are still the two most stable ones when the bridge atom S of ligand BHT is replaced by the other chalcogens of O, Se and Te. Further studies indicated that and both have room temperature dynamic stability and exhibit semiconducting. The exceptional stability and relatively narrow band gap make them advantageous over their inorganic counterparts. Our findings open opportunities to search for new 2D planar conducting coordination compound for organic electronic applications.